Population demographics of translocated northern bobwhites on fragmented habitat1. (29th December 2012) - Scott, Jason L.; Hernández, Fidel; Brennan, Leonard A.; Ballard, Bart M.; Janis, Michael; Forrester, N. David
Abstract Habitat fragmentation is considered a contributing factor to declining populations of northern bobwhite (Colinus virginianus). Some population strongholds exist within large expanses of habitat; however, many regions of the species' range have become fragmented and populations therein have become nearly extirpated. Our objectives were to determine whether combined habitat management and bobwhite translocation could restore bobwhite populations in habitat patches within a fragmented landscape. We translocated 550 bobwhites to 2 sites (≥660 ha; Caldwell and Fayette counties) in the Post Oak Savannah ecoregion of Texas, USA, during 2004–2006. We compared survival, home‐range size, and reproduction between translocated bobwhites in a fragmented landscape and resident bobwhites in contiguous habitat (Brooks County). Pooled over the 3‐year study, translocated bobwhites had lower survival (6 Apr–15 Aug, 2004–2006; Ŝ = 0.35; n = 165 bobwhites) than did resident bobwhites (Ŝ = 0.56; n = 224 bobwhites; P < 0.001). Translocated bobwhites also had larger home ranges ( <![CDATA[${\bar {x}}$]]> <inline-graphic xlink:href="ark:/27927/pgg40g3n25g" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> = 398.1 ha; n = 55 bobwhites) than resident bobwhites ( <![CDATA[${\bar {x}}$]]> <inline-graphic xlink:href="ark:/27927/pgg40g3n1zn" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> = 10.9 ha; n = 28 bobwhites; P = 0.003). Moreover, percent of hens nesting (95% CI = 36 ± 16.4%) and nesting rate (95% CI = 1.1 ± 0.2 nests/hen) were lower for translocated bobwhites than for resident bobwhites (79 ± 12.4% and 1.6 ± 0.3 nests/hen, respectively). Our restoration efforts were unsuccessful; relative abundance of bobwhites remained low (≤1.0 covey heard/point) on translocation sites despite intensive translocation efforts. Restoring bobwhite populations in areas with few remaining bobwhites may be beyond the realm of practical management in this fragmented ecoregion. © 2012 The Wildlife Society